2017
DOI: 10.1111/febs.14184
|View full text |Cite
|
Sign up to set email alerts
|

G3BP1 interacts directly with the FMDV IRES and negatively regulates translation

Abstract: RNA-protein interactions play a pivotal role in the function of picornavirus internal ribosome entry site (IRES) elements. Here we analysed the impact of Ras GTPase SH3 domain binding protein 1 (G3BP1) in the IRES activity of foot-and-mouth disease virus (FMDV). We found that G3BP1 interacts directly with three distinct sequences of the IRES element using RNA electrophoretic mobility-shift assays. Analysis of the interaction with domain 5 indicated that the G3BP1 binding-site is placed at the single-stranded r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 49 publications
2
42
0
Order By: Relevance
“…Recently, G3BP1 was reported to bind to the internal ribosome entry site (IRES) of FMDV and function as a translation inhibitor, and it was shown that FMDV 3C pro induced the cleavage of G3BP1 (59). Interestingly both the N-terminal and C-terminal G3BP1 cleavage products maintained the negative effect on translation (59).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, G3BP1 was reported to bind to the internal ribosome entry site (IRES) of FMDV and function as a translation inhibitor, and it was shown that FMDV 3C pro induced the cleavage of G3BP1 (59). Interestingly both the N-terminal and C-terminal G3BP1 cleavage products maintained the negative effect on translation (59).…”
Section: Discussionmentioning
confidence: 99%
“…G3BP1 associates directly to the three specific sequences of the internal ribosome entry site (IRES) elements of foot and mouth disease virus (FMDV) and the virus uses a similar mechanism to poliovirus to block G3BPs activity. During FMDV infection G3BP1 is also cleaved by its protease, 3C (3Cpro), yielding two fragments of G3BP (Ct-G3BP1, Nt-G3BP1) [121].…”
Section: Viral Targeting Of G3bps By Proteasesmentioning
confidence: 99%
“…First, Gemin5 was pulled down with the IRES elements of foot‐and‐mouth disease virus (FMDV) and hepatitis C virus (HCV) . Second, Gemin5 was proteolyzed in FMDV‐infected cells, a feature shared with essential factors involved in gene expression control, such as eIF4G and other RBPs . Cleavage of Gemin5 at the RKAR amino acid motif yields p85, which is then cleaved at the TKRL sequence yielding p57.…”
Section: Gemin5: Noncanonical Rbds Controlling Differential Expressiomentioning
confidence: 99%
“…[66] Second, Gemin5 was proteolyzed in FMDVinfected cells, [67] a feature shared with essential factors involved in gene expression control, such as eIF4G [68] and other RBPs. [69,70] Cleavage of Gemin5 at the RKAR amino acid motif yields p85, which is then cleaved at the TKRL sequence yielding p57. Both p85 and p57 are nonrepressive on IRES-dependent translation, although retain the capacity to interact with the IRES element.…”
Section: Gemin5 and Ires-dependent Translationmentioning
confidence: 99%